2013
DOI: 10.1002/jcb.24671
|View full text |Cite
|
Sign up to set email alerts
|

Energy Metabolism Characterization of a Novel Cancer Stem Cell‐Like Line 3ABOS

Abstract: Cancer stem cells (CSC) have a central role in driving tumor growth. Since metabolism is becoming an important diagnostic and therapeutic target, characterization of CSC line energetic properties is an emerging need. Embryonic and adult stem cells, compared to differentiated cells, exhibit a reduced mitochondrial activity and a stronger dependence on aerobic glycolysis. Here, we aimed to comparatively analyze bioenergetics features of the human osteosarcoma 3AB-OS CSC-like line, and the parental osteosarcoma M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
80
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(95 citation statements)
references
References 51 publications
7
80
0
Order By: Relevance
“…The metabolic phenotype of CSC/TICs is also controversially discussed; glioblastoma stem cells have been reported to be less[44] or more glycolytic than their daughter cells[45-47], or exhibit either phenotype in the same tumor[48]. Colon cancer or osteoblastoma CSC/TICs express higher levels of glycolytic genes[49] and are more glycolytic[50] than their differentiated counterparts. Our results indicate a more glycolytic and flexible metabolic function in the TICs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The metabolic phenotype of CSC/TICs is also controversially discussed; glioblastoma stem cells have been reported to be less[44] or more glycolytic than their daughter cells[45-47], or exhibit either phenotype in the same tumor[48]. Colon cancer or osteoblastoma CSC/TICs express higher levels of glycolytic genes[49] and are more glycolytic[50] than their differentiated counterparts. Our results indicate a more glycolytic and flexible metabolic function in the TICs.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study demonstrated the glycolytic nature of an osteosarcoma stem-like cell line with minimal contribution of OxPhos to cellular ATP production but a reduced mitochondrial function with a low spare respiratory capacity and coupling efficiency, and the lack of adaptive response to glucose deprivation[50]. It is unclear at this point if species or tissue differences, the choice of cells serving as comparisons and the choice of stem-cell markers for stem cell isolation impact these contradictory results, or if the generation of our TICs via IP enrichment from a primary cell line may also select for a specific phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, with respect to MG63 cells, 3AB-OS have fragmented mitochondria which rapidly networked in the presence of glucose-rich medium, whereas, growing in low glucose they entirely lose these structures. Overall, the findings suggested that the energy metabolism of 3AB-OS CSC strongly resemble that of normal stem cells and cancer cells which are characterized by a glycolytic anaerobic metabolism [20] .…”
Section: Research Highlightmentioning
confidence: 87%
“…Acquisition of certain mutations in key metabolic enzymes suggests that the metabolism of quiescent and self-renewing cells may also be biased towards glycolytic metabolism. Recent evidence from a variant human osteosarcoma cell line with cancer stem cell-like properties indicated greater dependence on glycolytic metabolism compared with parental cells (Palorini et al 2013). In addition, brain tumor-initiating cells have been shown to preferentially express the high-affinity neuronal glucose transporter, Glut-3, a Fig.…”
Section: Nuclear Mutations Affecting Energy Metabolismmentioning
confidence: 99%